Disciplinary roots and branches of evaluation: Some lessons from agricultural research - Horton, Douglas (International Service for National Agricultural Research, 1996)
Since its origins in North America in the 1960s, the field of program evaluation has grown considerably and its concerns have broadened from accountability to program improvement, decision support and institutional learning. Program evaluation is now commonly practiced in governmental organizations not only in North America but also in many countries of Western Europe and Oceania. Although program evaluation is a relatively new field with many controversies and lively debates, a unifying body of evaluation theory, methods and standards is gradually emerging. Evaluation has recently been described as a "transdiscipline" like statistics and measurement.